The Role of Human Security in Addressing the Inclusion of Women: Nuclear Security and the Women, Peace and Security Agenda in Jordan and Egypt - Yara Shaban; Jasmine Auda (International Journal of Nuclear Security, 2025)
This paper argues for a human security approach to women’s participation in nuclear security that stems from the larger Women, Peace and Security framework. This approach incorporates a gender perspective and a feminist lens that argues that women’s participation should extend beyond the diversity, equity, and inclusion initiatives to include an understanding of the centrality of women’s role from a human security approach in peacebuilding participation, negotiation, and conflict prevention. The paper explores this nexus by reviewing Egypt and Jordan’s approach to Women, Peace and Security and argues for framing women’s inclusion within a human security perspective. The review revealed a need to shift the discourse beyond enhancing women’s roles in disarmament efforts, conflict prevention, and post-conflict peacebuilding toward addressing broader peace and sustainability issues. The paper also advocates adopting a feminist viewpoint that recognizes women’s varied contributions to security within complex societal and geopolitical landscapes.
Keywords: Nuclear Security; Women; Peace; and Security Agenda; Gender Perspectives; Human Security; Diversity; Equity and Inclusion; Peacebuilding; Conflict Resolution.